EFFECT OF PLANT POPULATION ON CHARACTER EXPRESSION OF FIVE MUNGBEAN GENOTYPES UNDER DIFFERENT SOIL FERTILITY - Abdullah Taufiq; Afandi Kristiono (AGRIVITA, Journal of Agricultural Science, 2016)
Plant density and soil fertility are two components of micro environment affecting genetic expression. The research was conducted at Muneng Experiment Farm in Probolinggo from March to May 2013. Two factors consisted of five mung-bean genotypes (MMC679-2C-GT-2, MMC647d-GT-2, MMC554d-GT-2, MMC601f-GT-1 and Vima-1) and three levels of plant population (200,000, 333,333 and 500,000 plants ha-1) were evaluated at two soil fertility managements (with and without fertilization). The treatments were arranged in split plot design and replicated three times. All growth parameters observed were higher in more fertile soil. The increasing plant population triggered plants to grow taller, but reduced chlorophyll content index (CCI), number of trifoliate leaf per plant (LN), leaf area per plant (LA), total dry matter per plant (TDM), number of pods and seed weight, and nutrient uptake of individual plant. Grain yield production per unit area was not significantly different because of plant population compensation. All genotypes tested were suitable to be planted on population of 200,000 and 333,333 plants ha-1. With proper fertilization and population management, the genetic potential can be expressed by 3.5 t ha-1 for MMC554d-GT-2, 2.4 t ha-1 for MMC601f-GT-1 and Vima-1, 2.2 t ha-1 for MMC679-2C-GT-2, and 2.3 t ha-1 MMC647d-GT-2.